An educational tool for understanding MPEG‐2 videocompression and coding techniques - Fernández-Plazaola, Unai; Gómez-Paredes, Gerardo; López-Martínez, Francisco Javier (Willey Onlin Library, 2023)
The understanding of the video encoding/decoding processes is a key skill for students of computer science, engineering, or telecommunications, especially those specialized in multimedia. The special characteristics of the video signals, and how such features are leveraged to compress the video frames using coding theory, are hard to understand for engineering students. In this paper, we describe MPEG‐2 analyzer, an educational tool designed to provide a comprehensive and interactive way to understand MPEG‐2 video compression and encoding techniques. We have used our tool to evaluate its usefulness in reinforcing the knowledge about the MPEG‐2 video (de)coding process to Telecommunication Engineering students. Results show that the evaluation of the tool is very positive, and it has helped them to understand many of the complex concepts covered in the course.
Keywords: Educación - Innovaciones tecnológicas; Codificación, Teoría de la; MPEG; MPEG‐2; Video coding; Educational software; Compression